2022
DOI: 10.1002/adpr.202200019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of the Non‐Hermitian Radio Frequency Metasurface with Polarization‐Dependent Unidirectional Reflectionless Propagation

Abstract: Unidirectional reflectionlessness is one of the most fascinating effects at the exceptional point (EP) in a non‐Hermitian system. Herein, a polarization‐dependent non‐Hermitian radio frequency metasurface with unidirectional reflectionless (UR) phenomenon in dual frequency is proposed, which originates from the EP‐based effect. EP generation is observed in the loss‐assisted system by optimizing structure parameters. At EPs, when the incident light is x‐ or y‐polarized, ideal backward or forward reflectionlessn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…However, in practical applications, it can be cumbersome to introduce and manipulate gain factors in metamaterial platforms and to balance them with loss factors [33,34]. Recent research shows that all-passive systems without optical gain can be engineered to demonstrate EP-related phenomena [10,[35][36][37][38][39][40]. In [12], Li et al demonstrated a passive asymmetric acoustic absorber at an EP with a compact configuration and deepsubwavelength thickness which achieves EP-induced tunable asymmetric absorption.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practical applications, it can be cumbersome to introduce and manipulate gain factors in metamaterial platforms and to balance them with loss factors [33,34]. Recent research shows that all-passive systems without optical gain can be engineered to demonstrate EP-related phenomena [10,[35][36][37][38][39][40]. In [12], Li et al demonstrated a passive asymmetric acoustic absorber at an EP with a compact configuration and deepsubwavelength thickness which achieves EP-induced tunable asymmetric absorption.…”
Section: Introductionmentioning
confidence: 99%